(untitled) (LACCEI, 2024)
The countries of Latin America and the Caribbean, including Colombia, have sociocultural problems that prevent sustainable development among which are corruption, poverty: hunger, crime, class inequality, and culture permeated by various factors. One of these factors is the digital transformation and Digital Transformation with a Gender Approach - TCDEG - is a strategy that, due to its flexibility to facilitate the flow of information, allows for continuous dialogue between the different structuring actors of development and well-being represented in the quadruple helix: the State, the academic, the public society and the private society, this TDEG emphasizes closing the gap between men and women. The adjustments in the organization of the information and in the flow of processes are two necessary moments for the digital transformation and are based on the alignment of purposes for which the TDEG is made, although there are different methodologies for the formulation of indicators such as Balance Scorecard, Customer Supplier Approach, and Management Excellence Models, this work presents the methodology for the Formulation of Indicators of Cultural and Digital Transformation with a Gender and Culture approach in Colombia - FITCDEG - with which a battery of indicators was built to reduce, With the participation of the quadruple helix, the gender gaps in the Colombian academy are anchored in the digital transformation that is taking place in the state, the company, civil societies, and the academy itself.